Strategies and challenges in addressing ethical issues in the hospital context: A phenomenological study of nurse team leaders - Ni Made Nopita Wati; I Gede Juanamasta; Jutharat Thongsalab; Jintana Yunibhand (Belitung Raya Foundation, Indonesia, 2023)
Background: Nurse team leaders encounter considerable ethical challenges that necessitate using effective strategies to overcome them. However, there is a lack of research exploring the experiences of nurse team leaders in Indonesia who face ethical dilemmas in their professional duties. Objective: This study aimed to explore nurse team leaders’ experiences regarding strategies and challenges in dealing with ethical problems in hospital settings in Indonesia. Methods: This qualitative study employed a hermeneutic phenomenology design. Online semi-structured interviews were conducted between November 2021 and February 2022 among 14 nurse team leaders selected using a snowball sampling from seven hospitals (three public and four private hospitals). Van Manen’s approach was used for data analysis. Results: The strategies for overcoming ethical dilemmas included (i) seeking the facts, (ii) stepping back, (iii) considering support, and (iv) standing by patients. The challenges for the nurse team leaders in resolving ethical problems consisted of (i) seniority, (ii) trust issue, and (iii) lack of reflection and ethics training. Conclusion: Nurse team leaders recognize their specific roles in the midst of ethical challenges and seek strategies to deal with them. However, a negative working environment might impact ethical behavior and compromise the provision of quality care. Therefore, it is imperative for hospital management to take note of these findings and address issues related to seniority by providing regular ethics training and group reflection sessions to maintain nurses' ethical knowledge in hospital practice. Such interventions can support nurse team leaders in resolving ethical dilemmas and provide a conducive environment for ethical decision-making, ultimately improving patient outcomes.